Prevalence and Factors Associated with Meconium-Stained Amniotic Fluid in a Tertiary Hospital, Northwest Ethiopia: A Cross-Sectional Study - Enyew Abate; Kassahun Alamirew; Eleni Admassu; Awoke Derbie (Obstetrics and Gynecology International)
Background. Fetal bowel could pass meconium, a green viscous fluid, before or during labour and most intrauterine passage of meconium is associated with several fetomaternal factors that lead to increased risk of perinatal morbidity and mortality. Given that there is a paucity of data, this study was conducted to assess the proportion and associated factors of meconium-stained amniotic fluid (MSAF) in women who came for labour and delivery service in a tertiary hospital. Methods. A cross-sectional study was conducted from 1 June to 31 August 2018 among 606 labouring mothers at Felege Hiwot Referral Hospital, northwest Ethiopia. Study participants were selected using a systematic random sampling technique. Data were collected using an interviewer-administered pretested questionnaire and data checklist. Factors associated with MSAF were explored using multivariable logistic regression analysis. Results. MSAF occurred in 24.6% (149/606) of pregnancies. Nonreassuring fetal heart rate patterns (Adjusted Odds Ratio [AOR]: 21.9, 95% Confidence interval [95% CI]: 10.96–43.83), postterm pregnancy (AOR: 4.54, 95% CI: 2.24–9.20), duration of labour more than 15 hours (AOR: 2.83, 95% CI: 1.76–4.53), pregnancy-induced hypertension (AOR: 2.43, 95% CI: 1.45–4.05), oligohydramnios (AOR: 2.53, 95% CI: 1.25–5.12), interpregnancy interval less than 2 years (AOR: 2.24, 95% CI: 1.12–4.51), and monthly family income less than 5000 Ethiopian Birr (185 USD) (AOR: 2.03, 95% CI: 1.18–3.51) were significantly associated with MSAF. Conclusions. In this study, the proportion of MSAF was at 24.6% which was higher than a previous report in Ethiopia. Nonreassuring fetal heart rate pattern, postterm pregnancy, duration of labour more than 15 hours, pregnancy-induced hypertension, oligohydramnios, interpregnancy interval less than 2 years, and monthly family income less than 5000 Ethiopian Birr were factors associated with an increased risk for MSAF. Therefore, interventions aimed at detecting MSAF early should consider these factors.